Translation Strategies and Cultural Representation in Middle Eastern Restaurant Menus in Klang Valley, Malaysia - Amin Amirdabbaghian; Handoko Handoko; Syakirah Rifa’in@Mohd Rifain (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
This study examines the translation strategies used in the Klang Valley Region of Malaysia. The primary objectives of this research are to identify the most common strategies, analyze the effectiveness of the menu descriptions, and provide recommendations for improving translation practices in the food industry. A qualitative research design was employed, utilizing a frequency and descriptive analysis framework. Data were collected from a sample of Middle Eastern restaurant menus through convenience sampling. The strategies identified were categorized based on Vinay and Darbelnet’s model of translation strategies, while Nida and Taber’s componential analysis examined the effectiveness of the menu descriptions. The findings reveal that literal translation, transliteration, generalization, and cultural substitution are the most commonly used strategies, each with varying degrees of effectiveness in maintaining cultural integrity and communicative clarity. The results highlight the tension between preserving authenticity and ensuring comprehensibility, underscoring the importance of functional and culturally sensitive translation in multicultural food settings. This research contributes to the broader field of applied translation studies by shedding light on underexplored domains of culinary discourse and offers practical implications for menu translators, restaurateurs, and tourism stakeholders aiming to improve cross-cultural communication.